Evaluation of Anatomic Relationship Between Sural Nerve and Instrumentation During Mini-Open Achilles Tendon Repair: A Cadaveric Study. Issue 3 (September 2021) - Krautmann, Kurt; Shofoluwe, Ademola; Fowler, Brian; Stewart, Gary W.; Badana, Adrian N.S.
Abstract : The purpose of this study was to determine the relationship of the sural nerve to the Arthrex Percutaneous Achilles Repair System (PARS) jig and repair sutures. We performed cadaveric dissection on 10 unpaired above-knee amputation specimens (6 were right legs and 4 were left legs). In all but 1 cadaver, all of the sutures either punctured the nerve or passed anterior to it. Only 1 cadaver had sutures that were posterior to the sural nerve. In all cases, removal of the jig pulled the sutures through the nerve and the nerve was completely free after locking the sutures, and the sural nerve was within 1 cm of the lateral aspect of the transverse incision made for insertion of the jig. This cadaveric study revealed a high rate of sural nerve puncture when passing needles across the Achilles tendon using a commercially available minimally invasive repair device. This finding should caution users of Arthrex PARS jig to be attentive to postoperative symptoms of nerve injury. Level of Evidence: Diagnostic Level IV. See Instructions for Authors for a complete description of levels of evidence.